Are internal controls important in financial accountability? (Evidence from Lira District Local Government, Uganda) - Eton, Marus; Mwosi, Fabian; Ogwel, Bernard Patrick (Goodwood Publishing, 2022)
Purpose: The study examined the importance of internal control systems in financial accountability in Lira District Local Government, Uganda. Specifically, the study determined the importance of control activities, control environment, and monitoring of controls on financial accountability. Research methodology: A correlational design to establish the relationships between internal control systems and financial accountability, and regression analysis to explain the importance of internal controls on financial accountability were adopted. Results: Internal control systems account for 55.4% of the variations in financial accountability. Specifically, control environment and monitoring controls bear significant effects on financial accountability while control activities do not. Contribution: This is one of the original studies to assess Lira District Local Government. The study validates the contingent theory and extends its application in public administration. Limitations: The input of stakeholders from the community was ignored. Future researchers should consider investigating the role of community participation on the performance of district local governments in Uganda.